Effect of the Single or Combined Administration of Cocaine and Testosterone on Cardiovascular Function and Baroreflex Activity in Unanesthetized Rats - Engi, Sheila A. [UNESP]; Cruz, Fabio C. [UNESP]; Leao, Rodrigo M. [UNESP]; Correa, Fernando M.; Planeta, Cleopatra da Silva [UNESP]; Crestani, Carlos Cesar [UNESP] (Lippincott Williams & Wilkins, 2012)
Abuse of cocaine and androgenic-anabolic steroids has become a serious public health problem. Despite reports of an increase in the incidence of simultaneous illicit use of these substances, potential toxic interactions between cocaine and androgenic-anabolic steroids in the cardiovascular system are unknown. In the present study, we investigated the effect of single or combined administration of testosterone and cocaine for 1 or 10 consecutive days on basal cardiovascular parameters, baroreflex activity, and hemodynamic responses to vasoactive agents in unanesthetized rats. Ten-day combined administration of testosterone and cocaine increased baseline arterial pressure. Changes in arterial pressure were associated with altered baroreflex activity and impairment of both hypotensive response to intravenous sodium nitroprusside and pressor effect of intravenous phenylephrine. Chronic single administration of either testosterone or cocaine did not affect baseline arterial pressure. However, testosterone-treated animals presented rest bradycardia, cardiac hypertrophy, alterations in baroreflex activity, and enhanced response to sodium nitroprusside. Repeated administration of cocaine affected baroreflex activity and impaired vascular responsiveness to both sodium nitroprusside and phenylephrine. One-day single or combined administration of the drugs did not affect any parameter investigated. In conclusion, the present results suggest a potential interaction between toxic effects of cocaine and testosterone on the cardiovascular activity. Changes in baseline arterial pressure after combined administration of these 2 drugs may result from alterations in baroreflex activity and impairment of vascular responsiveness to vasoactive agents.
Keywords: abuse; anabolic steroids; cocaine; cardiovascular; hypertension; hypertrophy; vascular reactivity